2012
DOI: 10.3109/07420528.2012.655869
|View full text |Cite
|
Sign up to set email alerts
|

Altered Circadian Rhythm of Melatonin Concentrations in Hypocretin-Deficient Men

Abstract: Hypocretin deficiency causes narcolepsy. It is unknown whether melatonin secretion is affected in this sleep disorder. Therefore, in both narcolepsy patients and matched controls, the authors measured plasma melatonin levels hourly for 24 h before and after 5 days of sodium oxybate (SXB) administration. Although mean melatonin concentrations were similar between patients and controls, in narcoleptics the percentage of 24-h melatonin secreted during the daytime was significantly higher, and melatonin secretion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
3
7
0
Order By: Relevance
“…However, one study examining the pattern of melatonin secretion in narcolepsy with cataplexy found that though mean concentrations were similar to controls, there was a signifi cantly higher percentage of melatonin secreted during the day in those with narcolepsy [ 177 ]. This is consistent with another study demonstrating increased salivary melatonin during the day in narcoleptics with more severe daytime sleepiness [ 178 ].…”
Section: Melatonin and Hypersomniassupporting
confidence: 78%
“…However, one study examining the pattern of melatonin secretion in narcolepsy with cataplexy found that though mean concentrations were similar to controls, there was a signifi cantly higher percentage of melatonin secreted during the day in those with narcolepsy [ 177 ]. This is consistent with another study demonstrating increased salivary melatonin during the day in narcoleptics with more severe daytime sleepiness [ 178 ].…”
Section: Melatonin and Hypersomniassupporting
confidence: 78%
“…The results of this study originate from an extensive, constant routine protocol that was described previously (Donjacour et al ., ,b, ; Fig. ).…”
Section: Methodsmentioning
confidence: 94%
“…Owing to power limitations, we could not draw conclusions concerning the impact of phase-shifted melatonin secretion on sleep, sleepiness and fatigue. Former studies have reported on a delayed secretory melatonin pattern with peaks in the daytime in patients with delayed sleep-phase syndrome (33), whereas another study has observed a relatively higher melatonin secretion during the day in narcoleptic patients (34). Even though secondary narcolepsy is rarely seen, case descriptions of secondary narcolepsy in patients with hypothalamic tumour involvement have been reported (10,13,35,36,37,38).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%